2020
DOI: 10.1590/1678-992x-2018-0151
|View full text |Cite
|
Sign up to set email alerts
|

Climatic signal in a radial growth of Canadian and Maximovich poplars in south-western Poland

Abstract: The main goal set by researchers in this article was to gather knowledge on the structure of the basic biometric features of tree-rings of two species of poplars, belonging to different sections of Aegeiros-Populus xcanadensis and Tacamahaca-Populus maximowiczii, and to define and understand the correlation between weather and annual increment. A supplementary objective of the article was to determine pointer years of species found in individual populations. Our research used the standard methodology applied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ziemiańska and Kalbarczyk (2018) reported 5.37 mm GRW for SW of the Populus x canadensis Moench, which is around 3.3 times lower than the average GRW of this study. Remarkably lower averages (6.63 mm and 8.3 mm) were also reported by Ziemiańska et al (2020), including both SW and HW. In contrast, higher means, 19.8 mm (Erten and Önal 1995), 27.8 mm (LeBlanc et al 2020), 28.6 and 28.8 mm (Šēnhofa et al 2016, and 45 to 55 mm (DeBell et al 2002), were also reported for different poplar species.…”
Section: Physical Propertiesmentioning
confidence: 62%
“…Ziemiańska and Kalbarczyk (2018) reported 5.37 mm GRW for SW of the Populus x canadensis Moench, which is around 3.3 times lower than the average GRW of this study. Remarkably lower averages (6.63 mm and 8.3 mm) were also reported by Ziemiańska et al (2020), including both SW and HW. In contrast, higher means, 19.8 mm (Erten and Önal 1995), 27.8 mm (LeBlanc et al 2020), 28.6 and 28.8 mm (Šēnhofa et al 2016, and 45 to 55 mm (DeBell et al 2002), were also reported for different poplar species.…”
Section: Physical Propertiesmentioning
confidence: 62%
“…Under such circumstances, previously undervalued plant or animal taxa, including uncommon or introduced taxa, may gain ecological or economic significance. To monitor climate changes and their impact on forest ecosystems, the results of dendroclimatological research may be used [7][8][9][10][11][12][13][14][15][16]. Many of the introduced tree species are larger, grow faster, and have better wood value than European species [15].…”
Section: Introductionmentioning
confidence: 99%